2016
DOI: 10.5114/aoms.2015.50625
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and inflammation: evaluation with neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio

Abstract: IntroductionAssociation of vitamin D, inflammation and endothelial dysfunction, beside the classic bone metabolism disorders, may explain the pathogenesis of numerous diseases associated with vitamin D deficiency. While large numbers of reports support the relationship of vitamin D with inflammation, several reports fail to confirm this relationship. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are novel and inexpensive markers of inflammation that can be studied in all centers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 47 publications
7
38
2
4
Order By: Relevance
“…Ulcerative colitis patients with an affected distal part of the colon had limited inflammation [33,47]. It was shown that vitamin D plays an immunomodulatory role [48,49]. In a study conducted by Chang et al, stimulation of Th17 cells with the help of 1,25D 3 (depending on the concentration) induced expression of the C/EBP homologous protein (CHOP) -a particle involved in endoplasmic reticulum and translation inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Ulcerative colitis patients with an affected distal part of the colon had limited inflammation [33,47]. It was shown that vitamin D plays an immunomodulatory role [48,49]. In a study conducted by Chang et al, stimulation of Th17 cells with the help of 1,25D 3 (depending on the concentration) induced expression of the C/EBP homologous protein (CHOP) -a particle involved in endoplasmic reticulum and translation inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 Recent reports showed that serum levels of vitamin D have a negative correlation with the neutrophil/lymphocyte ratio (P o 0.001) but also with the platelet/lymphocyte ratio (P o 0.001), which is an independent marker of vitamin D deficiency. 84 This evidence suggests an inhibitory role on neutrophil-mediated inflammation exerted by vitamin D and its synthetic analogues (eg, TEI-A00114). 85,86 In patients with inflammatory disorders, such as acute exacerbation of chronic obstructive pulmonary disease, neutrophils undergo apoptosis through the p38MAPK signaling pathway due to the activity of vitamin 1α,25(OH) 2 D 3 .…”
Section: Role In Innate Immunitymentioning
confidence: 99%
“…Доказанным вкладом в нормализацию артериального давления является подавление витамином D синтеза ренина в клетках юкстагломерулярного аппарата почки [24,49,50]. Было показано, что витамин D уменьшает экспрессию гена ренина через рецептор-зависимый механизм, таким образом, уменьшая концентрации ренина и ангиотензина II, что в итоге приводит к снижению выработки альдостерона и улучшению течения артериальной гипертензии [51,52]. Однако, по данным метаа-…”
Section: дефицит витамина D и сердечнососудистые заболеванияunclassified